Association between dietary antioxidant levels and diabetes: a cross-sectional study - Zhou, Lei; Xu, Xiaoyu; Li, Yize; Zhang, Shuo; Xie, Hong (Frontiers in Nutrition, 2024)
Background The onset and progression of diabetes mellitus (DM) is strongly linked to oxidative stress. Previous studies have highlighted the protective effects of individual dietary antioxidants against diabetes. However, the relationship between a comprehensive combination of dietary antioxidants and diabetes has rarely been examined. Therefore, this study assessed the association between various dietary antioxidant intake levels and diabetes among US adults and further investigated potential associations using the Composite Dietary Antioxidant Index (CDAI). Methods The study employed data from the National Health and Nutrition Examination Survey (NHANES) conducted between 2011 and 2018 for cross-sectional analysis. Dietary information was obtained from two 24-h dietary recall interviews. The CDAI was calculated using intakes of six dietary antioxidants from the dietary information. Multifactorial logistic regression models were employed to investigate the association of different dietary antioxidants and CDAI with DM. The relationship between CDAI and DM was further explored using subgroup analyses and restricted cubic spline curves. Results A total of 7,982 subjects (mean age 47.32 ± 16.77 years; 48.50% male and 51.50% female) were included in this study. In the multivariate-adjusted single antioxidant model, vitamin C intake was significantly and negatively associated with diabetes prevalence (P for trend = 0.047), while zinc intake demonstrated a potential trend toward reduced diabetes risk (P for trend = 0.088). This association was similarly observed in the multivariate-adjusted model for the Composite Dietary Antioxidant Index (CDAI) in the female population (p = 0.046). Conclusion Intake of vitamin C was negatively associated with DM prevalence. Additionally, CDAI was found to reduce the risk of DM in the female population.